Implementasi Internet of Things (IoT) untuk Meningkatkan Kompetensi Siswa SMK Jakarta 1 - Ahmad Fitra Ritonga; Syafrima Wahyu; Frida Octavia Purnomo (Risenologi, 2020)
Internet of Things (IoT) needs to be developed in education and serves as one of the roles of education to face the industrial revolution 4.0. Vocational High School (SMK) is an appropriate level of education to prepare early for knowledge and application of IoT technology. Vocational High School Jakarta 1 has good technology but the competency of applying IoT expertise is still lacking. To improve the understanding and application of IoT, Physics Engineering Study Program of Binawan University proposes a solution in the form of training with the theme: Implementing Internet of Things (IoT) to improve student competence in Vocational High School Jakarta 1. This training aims to introduce about IoT especially implementation in the scheme monitoring by using light and temperature sensors to increase student motivation and competence in the industrial era 4.0. Based on the analysis of the data, it was concluded that the competency of student expertise could be significantly increased through IoT training to be accepted with significance level of 0.05. The method of implementing training is team work that is able to make the training more effectively and efficiently.